A balancing act: how interpreters affect the therapeutic alliance in psychotherapy with trauma-affected refugees—a qualitative study with therapists - Hanft-Robert, Saskia; Lindberg, Laura Glahder; Mösko, Mike; Carlsson, Jessica (Frontiers in Psychology, 2023)
Objective: The therapeutic alliance (TA) has the highest predictive value concerning the success of psychotherapy. The presented study aimed to explore how the presence of an interpreter affects the TA when working with trauma-affected refugees. Method: Semi-structured interviews were conducted with seven psychologists working in an outpatient clinic specialized in mental health care for migrant and refugee patients with trauma-related mental health problems in Denmark. Interviews were transcribed verbatim and analyzed using a structuring content analysis approach. Results: TA has been described as a dynamic therapist-interpreter-patient alliance triangle consisting of three distinct but highly intertwined and mutually influential dyadic alliances. Specific factors affecting the quality of the TA were identified, e.g. interpreter being emotionally attuned yet not overly involved; interpreter being barely visible yet present as a human being. Characteristics of trauma-affected refugee patients affecting the TA formation were also identified, e.g. a high level of personal distrust, different understandings of mental disorders and psychotherapy, stigmatization, perceptions of authorities. Conclusion: The presence of interpreters was perceived ambivalently and the formation of a good TA seems to be a balancing act. Based on the findings, recommendations for forming and maintaining a good TA in interpreter-mediated psychotherapy are provided.